Principais Causas de Condenações Totais e Parciais em Frangos de Corte e Ações do controle de Qualidade em Abatedouro Frigorífico Situado no Tocantins. - Sousa, Suellen Bezerra de (Universidade Federal do Tocantins, 2023)
The curricular internship was realized at the Agroindustrial Complex Aroldo Silva Amorim located in Aguiarnópolis in the state of Tocantins, subsidiary n° 501 of Bonasa Food Company. The study was performed in the quality control area under the supervision of the veterinary Fernanda Alcântara coordinator of quality control and in the Federal Inspection Service No. 1213 under the supervision of Daniella Dandi Freitas Sousa, federal inspection service. This stage was carried out under the leading of Dr. Catia Maria de Oliveira Lobo during the period from 16 May to 22 July 2016, totalizing 376 hours. During the internship was conducted monitoring of the stages of slaughter, the monitoring carried out by the quality control industry company through implemented sef-control plans and inspection ante and post mortem. Data collection realization about the main causes of total and partial convictions during the period from 20 June to 20 July 2016, a total of 1,680,893 birds slaughtered, among which the major causes of partial convictions were contusions / fracture, dermatosis and bile contamination, and the total condemnation of colibacillosis, disgusting aspect and inadequate bleeding.